Mídia e ódio: como a agressividade da audiência no ambiente digital impacta a relação leitor-jornal - Ogawa, Alfredo (2019)
Demonstrations of audience hatred in the digital environment are the most obvious, troublesome and growing tip of the current reader-newspaper relationship. This dissertation explored the implications – almost always negative but some surprisingly positive – of the new association between those consuming and producing news brought about by the advancement of technology. The research sought to identify the characteristics and consequences of the clash between the media and the public, when the latter abandoned a historically limited role and appropriated digital tools, notably the reports online area of comments, to challenge the media in their own spaces. The theoretical foundation rested on the thinking of Hobbes (2004), Arendt (1994) and Baitello (1999) to question the reductive view adopted by many, including the press, that hatred is irrational and therefore purposeless. In historicizing the reader-newspaper link since the seventeenth century, the study presented the strategies of the media to regulate the participation of the audience, maintaining, in the definition of Pross (1980), a rigid vertical hierarchy of values. The evaluation of 20 000 comments in Folha de S.Paulo's social network account was the practical part, divided into a qualitative content analysis with methodology proposed by Bardin (1995) and, given the volume of material, a quantitative use of the software Sobek, from Universidade Federal do Rio Grande do Sul. The study showed the inefficacy of the barriers created by the press to curtail the audience on the internet. It noted that newspapers and journalists seek to dehumanize the so-called haters in order to disqualify and ignore more aggressive manifestations. It also showed that, in fact, the authors of hate messages can be divided into distinct groups in their intentions. Among these goals is the denial of the media, with acid criticism of its credibility and authority to inform. The research also showed how hatred represents part of the thinking of public opinion and that, in Folha's analyzed case, it signaled a relevant reality of the country that did not appear at the time on the pages of the diary. The conclusion shows that the reader-newspaper link has been definitely altered by technology and that the press loses by stigmatizing and avoiding haters, when evidence shows that they, in their own way and however unpleasant, help to understand society the vehicles cover in a daily basis